La princesa and the pea - Elya, Susan Middleton, 1955- (G. P. Putnam's Sons, 2017)
"A rhyming twist on a classic fairy tale in which a queen places a pea under a young lady's mattress to see if she is truly a princess. Incorporates Spanish words and Includes a glossary"--